Reduction of In-Band Interferences’ Effect Using Subspace Algorithms in Radio Channel Data - Seda ÜSTÜN ERCAN; Hülya GÖKALP (International Journal of Applied Methods in Electronics and Computers, 2016)
In-band interference increases the noise floor of delay profiles estimated from frequency modulated continuous wave (FMCW) sounder channel data and prevents weak multipath components from being detected. In this study two of the subspace methods named MUltiple SIgnal Classification (MUSIC) and EigenVector (EV) algorithm were used to reduce the effect of interference in delay profiles obtained from an FMCW channel data, and the results are compared with those from conventional FFT method. Results show that MUSIC and EV methods have similar results for time delay estimation, and perform better than the FFT method.